Residual Risk Accounting: A Pilot Study. (15th April 2015) - Farrow, Scott
Abstract : Risks such as flooding, oil spills, deaths, and unemployment continue despite numerous policies to prevent and mitigate their effects. Such policies are typically analyzed in their natural units such as jobs making comparison difficult across categories. An approach akin to a satellite national income and product account (NIPA) allows direct comparison of the relative importance and variability of these residual risks. Results are presented for an unusual geographic aggregate associated with coasts. Although this framing adds difficulties for integration into national accounts, precedents exist. The findings synthesize elements that would otherwise be separated or not reported in standard NIPA accounts. Some elements are found to be stable and large, while other elements exhibit high variability and a high level of damages potentially informing individual and policy choices. The pilot case study also suggests the value of using a more standard, national geographic area.